PENYULUHAN PENTINGNYA PEMBERIAN ASI EKSLUSIF DAN MANFAATNYA PADA IBU DAN BAYI DI DESA SOPA KECAMATAN KINDANG KABUPATEN BULUKUMBA - Husnul Khatimah; Kurniati Akhfar; Nadiatul khaera (JCS, 2021)
Exclusive breastfeeding is breastfeeding during the .first 6 months of a baby's life without food or other drinks except vitamins, drugs and ORS. Breast milk functions as an antibody, fulfilling the nutritional intake of the baby and reduces the rate of morbidity and infant mortality. Breast milk is the best food for the baby when he/she was born. Many researches prove that breast milk is the best and primary food for the baby because in the breast milk contain an antibody that the baby need to resist any kind of disease. The excellence of breast milk has been prove, however the tendency of the mother not to give an exclusive breast milk to their baby is bigger. It is influenced by some factors, such as occupation, age, and education.This studyisto know the relation between the knowledge of the mother about usefulness of the breast milk for the baby with exclusive breast milk. The method used in this community service is to conduct counseling and distribute leaflets to find out the differences in mother's knowledge about exclusive breastfeeding